Evaluation of New Passive Heating Systems for Low-Cost Greenhouses in a Mild-Winter Area - Santiago Bonachela; María Cruz Sánchez-Guerrero; Juan Carlos López; Evangelina Medrano; Joaquín Hernández (Horticulturae, 2025)
The main objective of this work was to evaluate new variants of passive heating systems used for horticultural crop cycles planted in the cold period in low-cost greenhouses on the Mediterranean Spanish coast (a mild-winter area). The double low cover (DLC) is variant of the conventional fixed plastic screen that reduces the air volume and increases the airtightness around crops. Three identical DLCs were installed inside a typical greenhouse, and the microclimate measured in the three DLCs was similar. The DLCs reduced the solar radiation transmissivity coefficient by around 0.05 but increased the mean daily substrate and air temperatures (up to 1.6 and 3.6 °C, respectively). They also modified the air humidity, although this can be modulated by opening the vertical sheets located on the greenhouse aisles (DLC vents). The black plastic mulch forming an air chamber around the substrate bags (BMC), a new mulch variant used in substrate-grown crops, increased the substrate temperature with respect to the conventional black mulch covering the entire ground surface. The combination of BMC plus DLC increased the mean daily substrate temperature by up to 2.9 °C, especially at night. Low tunnels covered with transparent film and with a spun-bonded fabric sheet were also compared, and both materials were efficient heating systems regarding substrate and air temperatures. Low tunnels combined with the DLC substantially increased air humidity, but this can be partially offset by opening the DLC vents. The combination of low tunnels and DLC does not seem recommendable for greenhouse crops planted in winter, since both systems reduce solar radiation transmissivity.